Diabetes prevention program in a Mediterranean environment: Individual or group therapy? An effectiveness evaluation. Issue 2 (April 2015) - Endevelt, R.; Peled, R.; Azrad, A.; Kowen, G.; Valinsky, L.; Heymann, A.D.
Highlights No statistically significant differences were detected between the two intervention groups in age; gender and clinical measurements at recruitment. Thirty nine percent of both groups developed diabetes and entered the Diabetes Registry by 2012. The mean time from 2005 until entry to the Diabetes Registry was 2.9 and 2.5 years for the individual and group therapy respectively. Both interventions were equally reduced the risk factors. For large health organizations with a high number of pre-diabetes patients and scarce resources, group therapy, where twelve people are reached out by one team member are preferable and more costly effective, than a one on one therapy.